2021
DOI: 10.1186/s11671-021-03522-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Osteoinductive Effects of Hydroxyapatite Nanoparticles on Mesenchymal Stem Cells by Endothelial Cell Interaction

Abstract: Nano-hydroxyapatite (nano-HA) has attracted substantial attention in the field of regenerative medicine. Endothelial cell (EC)-mesenchymal stem cell (MSC) interactions are necessary for bone reconstruction, but the manner in which nano-HA interacts in this process remains unknown. Herein, we investigated the cytotoxicity and osteoinductive effects of HA nanoparticles (HANPs) on MSCs using an indirect co-culture model mediated by ECs and highlighted the underlying mechanisms. It was found that at a subcytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…It has been demonstrated that HIF‐1α can induce the transformation of bone marrow stem cells into osteoblasts 55,56 . Researchers 57 found that hypoxia‐induced HIF‐1α promotes osteoblast expression of BMP‐2 and promotes new osteogenesis by synergizing with the ILK/Akt/mTOR signaling pathway.…”
Section: The Possible Mechanism By Which Hif‐1α Promotes Bone Regener...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that HIF‐1α can induce the transformation of bone marrow stem cells into osteoblasts 55,56 . Researchers 57 found that hypoxia‐induced HIF‐1α promotes osteoblast expression of BMP‐2 and promotes new osteogenesis by synergizing with the ILK/Akt/mTOR signaling pathway.…”
Section: The Possible Mechanism By Which Hif‐1α Promotes Bone Regener...mentioning
confidence: 99%
“…has been demonstrated that HIF-1α can induce the transformation of bone marrow stem cells into osteoblasts. 55,56 Researchers 57 found that hypoxia-induced HIF-1α promotes osteoblast expression of BMP-2 and promotes new osteogenesis by synergizing with the ILK/Akt/ mTOR signaling pathway. Patients with postmenopausal osteoporosis have abnormal proliferation of adipose tissue within the bone marrow 58,59 and decreased bone regenerative capacity.…”
Section: Hif-1α With Osteoblastsmentioning
confidence: 99%
“…Along with the growth factors, a number of leucocytes may also be present in the i-PRF which might have an anti-inflammatory effect [ 41 ] thus aiding in better healing of the tissues. (Abd El Raouf et al, 2019) [ 42 ] Along with nano-HA bone graft, i-PRF can have an osteoinductive effect on the neighbouring cells due to the release of growth factors and bone morphogenetic proteins [ 43 , 44 ]. Hence, the nano-HA crystalline bone graft showed better comparable results when used with i-PRF.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (HA), as a commonly used inorganic biomaterial, loaded with co-overexpressed osteogenic factor semaphoring 3A (Sema3A) and HIF-1α modified MSCs, promotes osteogenic differentiation [ 178 , 179 ]. Furthermore, Nano-HA stimulates ECs to produce HIF-1α dose-dependently and upregulate osteogenic genes via the ERK1/2 signal pathway, increasing mineralized nodules and ALP [ 180 ]. Cu-Li-doped Nano-HA (Cu-Li-nHA) upregulates HIF-1α and stromal cell-derived factor-1 (SDF-1) by steadily releasing Cu 2+ , then promotes angiogenesis and induces BMSCs homing to necrotic areas, stimulating BMSCs to differentiate into osteoblasts through Wnt/GSK-3β/β-catenin pathway [ 181 , 182 , 183 ].…”
Section: Hif-1α Involvement In the Bone Repair Of Biomaterialsmentioning
confidence: 99%